2024
DOI: 10.1111/iji.12664
|View full text |Cite
|
Sign up to set email alerts
|

The role of monocyte/macrophage chemokines in pathogenesis of osteoarthritis: A review

Hao Luo,
Linfeng Li,
Song Han
et al.

Abstract: Osteoarthritis (OA) is one of the most common degenerative diseases characterised by joint pain, swelling and decreased mobility, with its main pathological features being articular synovitis, cartilage degeneration and osteophyte formation. Inflammatory cytokines and chemokines secreted by activated immunocytes can trigger various inflammatory and immune responses in articular cartilage and synovium, contributing to the genesis and development of OA. A series of monocyte/macrophage chemokines, including monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 144 publications
0
0
0
Order By: Relevance
“…The culture supernatants were subjected to cytokine array analysis. We observed that VB1 treatment markedly reduced the production of CCL2, a potent pro-OA mediator ( 7 ), in macrophages ( Fig. 2 D ).…”
Section: Resultsmentioning
confidence: 75%
“…The culture supernatants were subjected to cytokine array analysis. We observed that VB1 treatment markedly reduced the production of CCL2, a potent pro-OA mediator ( 7 ), in macrophages ( Fig. 2 D ).…”
Section: Resultsmentioning
confidence: 75%
“…The CCL2/CCR2 axis has been demonstrated to regulate inflammation in OA and other pathological conditions ( 115 ). Some previous studies showed that this axis orchestrates an intricate cellular choreography during OA pathogenesis ( 66 , 116 , 117 ). In OA, the dynamic interplay between CCL2 and CCR2 is mediated by synovial tissues, chondrocytes, and infiltrating immune system cells.…”
Section: The Intricate Dance: Ccl2/ccr2 Axis In Osteoarthritismentioning
confidence: 99%
“…Previous study indicates patients with carotid atherosclerosis exhibit elevated plasma levels of CXCL13, especially in symptomatic cases, and higher CXCL13 expression within atherosclerotic carotid plaques compared to nonatherosclerotic vessels 77 . CCL8 is a potent chemoattractant for monocytes and macrophages, directing them to areas of inflammation and infection 78,79 . Retnla hi Ear2 hi Mφ in WT mice show higher enrichment in ERK1 and ERK2 cascade, positive regulation of angiogenesis, and lipid storage (Figs.…”
Section: Differential Effects Of Saa3 Deficiency On Macrophage Subpop...mentioning
confidence: 99%